Factors Affecting the Society’s Preference Using Zakat, Infaq And Alms Based Crowdfunding Platform - Rahmah, Fitria (Borneo International Journal of Islamic Studies, 2022)
Poverty is an economic problem that has not yet been resolved. Various concepts are offered to overcome the problem of poverty, one of which is offered by Islam by utilizing the instruments of Zakat, Infaq and alms as a means of distributing wealth from the rich to those in need. In order to optimize the collection of ZIS funds, several breakthroughs were made, one of which was through the Social Crowdfunding platform, such as kitabisa.com. Therefore, this study aims to determine the role of the Kitabisa.com platform in raising awareness until finally deciding to channel ZIS funds on the Kitabisa.com platform. This research is included in field research with quantitative methods. The data used is sourced from primary data collected directly from respondents using google form, while secondary data is sourced from articles, books, internet. The data that has been collected is analyzed using SEM-PLS with the help of the SmartPLS analysis tool. The results showed that the accountability variable had a positive and significant effect on the decision to distribute ZIS on the social crowdfunding platform kitabisa.com, while the other variables had no significant effect.